Mechanically evolving and solvent-responsive waste-valorized poly (methacrylated β-keratin) organogel nanostructures and exogel spatiotemporal transition property - Yoobsan Ejeta Amensisa; Chia-Kuan Lin; Chih-Chia Cheng; Chang-Mou Wu; Chien-Hsing Lu; Jem-Kun Chen (Chemical Engineering Journal, 2026)

Evolution of swine influenza surveillance and one health governance in Taiwan: from zoonotic risk management to integrated preparedness - Cheng-Han Lin; Tzu-Min Lin; Meng-Wei Lin; Chih-Sheng Lin (Veterinary Research Communications, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

First visualization of intact sperm storage tubules in the duck oviduct: A fluorescent labeling approach for targeted SST sampling - Hsiu-Lien Herbie Lin; Chin-Hui Su; Shih-Yi Huang; Ya-Hsin Kuo; Liang-Yuan Wei; Yi-Ying Chang; Ching-Wei Chang; Jeng-Fang Huang; Pascal Mermillod; Chih-Hsiang Cheng (Animal Reproduction Science, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Artificial intelligence-enabled flexible surface-enhanced Raman scattering substrate based on silver nanoparticles/polypyrrole/chitosan film for sensitive uric acid detection in saliva, serum and urine - Nazar Riswana Barveen; Petchi Raman Mariappan; Sathishkumar Chinnapaiyan; Yen-Yu Lin; Chih-Yu Kuo; Yu-Wei Cheng (Carbohydrate Polymers, 2026)

A temperate group living in the subtropics: evolutionary history and integrative taxonomy of the pseudoscorpion genus Allochthonius Chamberlin, 1929 (Pseudoscorpiones: Pseudotyrannochthoniidae) in Taiwan - Hsiang-Yun Lin; Danilo Harms; Ren-Chung Cheng; Chih-Han Chang (Organisms Diversity & Evolution, 2026)

Ensemble learning: a study on the border inspection prediction model for high-risk products adulterated with Sudan Red in Taiwan - Li-Ya Wu; Wei-Chih Cheng; King-Fu Lin; Jia-Jhen Lee; Wen-Chou Lin; Hsu-Yang Lin; Chia-Yen Lu; Chih-Kang Chiang (Food Control, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Dexmedetomidine Mitigates Sevoflurane-Induced Neurodevelopmental Effects in Paediatric Anaesthesia: A Meta-Analysis and Preclinical Study - Hsuan-Chih Lao; Chia-Wei Huang; Ssu-Han Wang; Yen-Lin Su; Chien-Hui Chang; Cheng-Yen Liao; Jen-Chieh Wu; Ying-Chun Lin; Jin-Wu Tsai (Journal of Neuroimmune Pharmacology, 2026)
Sevoflurane (Sevo) anaesthesia in children is linked to an increased incidence of postoperative emergence agitation (EA) and potential neurotoxicity in developing brains. However, the specific risks of subanaesthetic foetal or neonatal exposure to Sevo remain unclear. This study evaluates the safety and efficacy of combining dexmedetomidine (Dex) with Sevo to manage EA in paediatric anaesthesia. A systematic review and meta-analysis of randomized controlled clinical trials involving children under 8 years old revealed that Dex significantly reduces EA incidence when administered via intravenous, perineural, and intranasal routes. Using in utero electroporation, we found that pregnant mice exposed to 2.5% Sevo at embryonic days 14.5 and 15.5 exhibited transient neuronal migration deficits, with 25% of neurons delayed in deeper cortical layers. However, these neurons migrated to the cortex by postnatal day 8. Neonatal mice exposed to 2.5% Sevo experienced a 10% reduction in dendritic spine density in adolescence, associated with impaired somatosensory function, as assessed by the Von Frey test. Remarkably, Dex pretreatment ameliorated these pathological and functional changes. Thus, foetal or neonatal Sevo exposure can delay neuronal migration and reduce dendritic spine density. Dex co-administration effectively mitigates these adverse outcomes, supporting its potential use in paediatric anaesthesia to protect developing brains. Graphical abstract

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Combined exposure to microplastics and cadmium alters gut microbiota composition in preschool children: A cross-sectional study - Chi-Sian Kao; Chuen-Bin Jiang; Chih-Chieh Yang; Ying-Lin Wang; Yi-Hua Chen; Hsing Jasmine Chao; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Hazardous Materials, 2026)

Smart SERS platform with a machine-learning approach for the detection of thiram in fruit juices using an Ag NPs/NiFeLDH/MXene composite - Nazar Riswana Barveen; Petchi Raman Mariappan; Sathishkumar Chinnapaiyan; Yen-Yu Lin; Chih-Yu Kuo; Yu-Wei Cheng (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Long-term quality assessment of the vacuum-sealed salted and honey-roasted peanuts after 30 years of storage based on lipid stability, volatile compounds, and olfactory characteristics - Yan-Cheng Lin; Robin Yih-Yuan Chiou; Chih-Yu Lo (Food Research International, 2025)

Analytical and usability comparison of microsampling dried blood spot devices for glucocorticoid detection in sports using ultra-high-performance liquid chromatography–tandem mass spectrometry - Cheng-Chia Chen; Yu-En Lin; Mei-Chich Hsu; Yu-Chuan Lin; William Chih-Wei Chang (Analytica Chimica Acta, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Sediment characteristics affecting natural radionuclide distribution and radiological assessment in a tropical wetland near Maanshan Nuclear Power Plant, Southern Taiwan - Ting-Chien Chen; Yi-Lung Yeh; Fan-Cheng Zeng; Chih-Chung Lin; Zhi-Mou Chen; Wei-Hsiang Huang (Environmental Monitoring and Assessment, 2025)

Manipulation of carbon dioxide adsorption and desorption via CO₂-philic fibrous polyethyleneimines under alternating current electric fields by frequency tuning - Chih-Wei Chen; Yi-Hua Lin; Chih-Chia Cheng; Chien-Hsing Lu; Jem-Kun Chen (Science of The Total Environment, 2025)

Association between air pollution and obstructive sleep apnea in terms of respiratory event frequency and lung-to-finger circulation time - Rachel Chien; Zhihe Chen; Peizheng Wang; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Arnab Majumdar; Jiunn-Horng Kang; Kang-Yun Lee; Wun-Hao Cheng; Yi-Chih Lin; Cheng-Jung Wu; et al. (Atmospheric Pollution Research, 2025)

Pediatric Abdominal and Pelvic CT Scans and the Subsequent Risk of Malignancy and Benign Genital Tumors: A Retrospective Cohort Study - Feng-Yi Su; Chih-Feng Chen; Kevin Chih-Yang Huang; Cheng-Li Lin; Fuu-Jen Tsai; Jui-Ting Hsu; Shin-Lei Peng (Journal of Medical and Biological Engineering, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Establishing coastal partnerships for sustainable development in Taiwan: A case of Shanshui area, Penghu - Wen-Hong Liu; Hsiao-Chien Lee; Shingo Akaike; Li-Shu Chen; Chih-Cheng Lin; Hu Chun-Chieh; Kuei-Chao Chang (Marine Policy, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Five novel RNA viruses of the invasive big-headed ant (Pheidole megacephala) - Charly T. Hartle; Chih-Chi Lee; Hung-Wei Hsu; Chun-Yi Lin; Kuan-Ling Liu; Joey Yin-Xin Chang; John A. Lawrence; Jia-Wei Tay; Chin-Cheng Scotty Yang (Archives of Virology, 2025)
The African big-headed ant, Pheidole megacephala , is one of the most destructive invasive ant species, posing a significant threat to native biodiversity and ecosystem function, particularly in island ecosystems. Despite recent efforts to characterize pathogens in other major invasive ants, P . megacephala has received comparatively little attention. In this study, we characterized five novel RNA viruses actively replicating in P . megacephala , which we have named Pheidole megacephala virus 1–5 (PmV1-5), and examined viral diversity and prevalence in two invasive populations in Taiwan and Hawaii. This ant possesses a unique trait of true morphological worker dimorphism (major and minor), allowing us to test whether virus prevalence differs between the major and minor worker castes. Our findings indicate that all five novel viruses were present in both populations, but viral prevalence was higher in Hawaii than in Taiwan, potentially due to differences in supercolony structure. Multiple-virus infections were common, with coinfection by PmV1 and PmV5 being the most frequent. Notably, we found no significant difference in infection patterns between major and minor workers, suggesting that virus distribution is stable within colonies and that sampling different castes does not introduce bias in pathogen detection. This study represents the first characterization of viral pathogens in P . megacephala and may contribute to the development of microbial control strategies against this globally invasive ant.

A review of umami taste of Tea: Substances, perception mechanism, and physiological measurement prospects - Yashu Yu; Xiaoxiao Feng; Imre Blank; Haoli Wang; Yiwen Zhu; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Trends in Food Science & Technology, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Protecting Migrant Labor Rights in the Distant-Water Fisheries Sector: A Comparative Analysis of the Legal Framework of Three Major Fishing Nations in Eastern Asia - Wen-Hong Liu; Po-Chih Hung; Peter Vandergeest; Azmath Jaleel; Bruno Ciceri; Chih-Cheng Lin (Reviews in Fisheries Science & Aquaculture, 2025)

High sensitivity mercury ion detection via thermal shock and quench with molecular sieve-functionalized FETs - Guan-Cheng Zeng; Hsuan-Wei Huang; Chia-Kai Lin; Jung-Chih Chen; Sheng-Chun Hung; Guo-Chun Dong; Yu-Lin Wang (Chemical Engineering Journal, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Mercerized bacterial cellulose/chitosan/waterborne polyurethane composites for sustainable and effective food preservation packaging - Cheng-Ying Li; Jhu-Lin You; I-Tseng Liu; Annisa Istiqomah; Ying-Chih Liao (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Toward Sustainable Fisheries: Lessons Learnt from Taiwan’s Offshore and Coastal Fishery Policy - Kuo-Huan Ting; Hao-Tang Jhan; Chih-Cheng Lin; Wen-Hong Liu (Coastal Management, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

The influence of PM2.5 exposure on SARS-CoV-2 infection via modulating the expression of angiotensin converting enzyme II - Meng-Wei Lin; Cheng-Han Lin; Jia-Rong Chang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chih-Sheng Lin (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Comprehensive evaluation of air quality: incense burning and night market emissions in Kaohsiung, Taiwan, using the ISCST3 air quality model - Pei-Cheng Cheng; Kassian T. T. Amesho; Yin-Cheng Huang; Yuan-Chung Lin; Feng-Chih Chou; Tsu-Nai Wang; Pei-Shih Chen; Kang-Shin Chen; Ken-Lin Chang; Chien-Hung Lee (Air Quality, Atmosphere & Health, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

Exploration of the flavor diversity of oolong teas: A comprehensive analysis using metabolomics, quantification techniques, and sensory evaluation - Xiaoxiao Feng; Haoli Wang; Yashu Yu; Yiwen Zhu; Jingke Ma; Zhibin Liu; Li Ni; Chih-Cheng Lin; Kequn Wang; Yuan Liu (Food Research International, 2024)

Role of HIF-1α-Activated IL-22/IL-22R1/Bmi1 Signaling Modulates the Self-Renewal of Cardiac Stem Cells in Acute Myocardial Ischemia - Wei Lee; Syuan-Ling Lin; Chih-Sheng Chiang; Jui-Yu Chen; Wee-Wei Chieng; Shu-Rou Huang; Ting-Yu Chang; B. Linju Yen; Mien-Chie Hung; Kuan-Cheng Chang; Hsu-Tung Lee; Long-Bin Jeng; et al. (Stem Cell Reviews and Reports, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Identification of organic constituents on atmospheric particulate matter in the East Asian background air of free troposphere by GC×GC-TOFMS - Chang-Feng Ou-Yang; Yi-Jun Chen; Hsin-Cheng Hsieh; Chung-Te Lee; Kai-Hsien Chi; Neng-Huei Lin; Chih-Chung Chang; Jia-Lin Wang (Chemosphere, 2024)

Book review - Wen-Hong Liu; Chih-Cheng Lin (Marine Policy, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Experimental study of high-mode buckling behavior of flat steel core in a buckling-restrained brace - Pao-Chun Lin; Chih-Wei Chang; Bing-Cheng Wu (Engineering Structures, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

The changes and the potential clinical applications of cytokines in Taiwan’s major venomous snakebites patients - Chih-Chuan Lin; Chia-Cheng Wang; Chun-Hsiang Ou Yang; Chien-Chun Liu; Jau-Song Yu; Wen-Chih Fann; Yen-Chia Chen; Chia-Pang Shih (Toxicon, 2024)

Urine cadmium and urolithiasis: A systematic review and meta-analysis - Yuan-Hsin Chen; Chih-Fu Wei; Ya-Yun Cheng; Carol Mita; Chinh Lu Duc Hoang; Cheng-Kuan Lin; Yu-Tzu Chang; David C. Christiani (Environmental Research, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

Metabolomic profiling of maternal plasma identifies inverse associations of acetate and urea with anti-SARS-CoV-2 antibody titers following COVID-19 vaccination during pregnancy - An-Shine Chao; Chiao-Yun Lin; Meng-Han Chiang; Kuan-Ying Lu; Cheng-Kun Tsai; Kuan-Ju Chen; Chih-Wei Chien; Ting-Shu Wu; Yao-Lung Chang; Angel Chao; Gigin Lin; Chih-Yung Chiu (Journal of Molecular Medicine, 2024)

Enhanced photodegradation of pentafluoropropionic acid (PFPA) via TiO2-synthetic zeolite composites: A sustainable approach for effective defluorination - Subham Halder; Feng-Chih Chou; Tsz-Kin Wan; Yi-Tien Tsai; Pei-Cheng Cheng; Yuan-Chung Lin (Journal of Water Process Engineering, 2024)

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

Dinaciclib inhibits the growth of acute myeloid leukemia cells through either cell cycle-related or ERK1/STAT3/MYC pathways - Chieh-Lin Jerry Teng; Pang-Ting Cheng; Yu-Chiao Cheng; Jia-Rung Tsai; Mei-Chih Chen; Ho Lin (Toxicology in Vitro, 2024)

Self-synthesis and performance analysis of a Cu-Fe composite ZSM-5 zeolitic catalyst for NOx reduction and particulate matter removal using NH3 SCR - Shivani Shirke; Feng-Chih Chou; Yu-Zheng Wang; Pei-Cheng Cheng; Shang-Cyuan Chen; Yuan-Chung Lin (Journal of Environmental Chemical Engineering, 2024)

Toward sustainable development of tuna longline fishery in Taiwan: Value chain analysis - Wen-Hong Liu; Chih-Cheng Lin; Cheng-Feng Lee; Chien-Shu Tsai; Tsung-Yu Yang (Marine Policy, 2024)

Multidimensional exploration of the bitterness amelioration effect of roasting on Wuyi Rock tea - Weiying Su; Li Ni; Yizhe Chen; Daoliang Wang; Chih-Cheng Lin; Yuan Liu; Zhibin Liu (Food Chemistry, 2024)

Unveiling the aromatic intricacies of Wuyi Rock Tea: A comparative study on sensory attributes and odor-active compounds of Rougui and Shuixian varieties - Daoliang Wang; Zhibin Liu; Xiaoye Lan; Cainan Wang; Wensong Chen; Sijia Zhan; Yaqian Sun; Weiying Su; Chih-Cheng Lin; Wei Liu; Yuan Liu; Li Ni (Food Chemistry, 2024)

Potential beneficial effects of long-term aspirin use on the prevalence of colorectal cancer: a population-based study of the US Nationwide Inpatient Sample - Ko-Chao Lee; Kuan-Chih Chung; Hong-Hwa Chen; Kung-Chuan Cheng; Kuen-Lin Wu; Ling-Chiao Song (Cancer Causes & Control, 2024)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Phthalate esters and nonylphenol concentrations correspond with microplastic distribution in anthropogenically polluted river sediments - Ming-Huang Wang; Chih-Feng Chen; Frank Paolo Jay B. Albarico; Shan-Lu Lin; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2024)

Active packaging incorporating chitosan, casein phosphopeptide, and plasmonic modification to maintain quality and regulate the respiration rate of fresh-cut Pyrus serotina Rehder during storage - Chao-Kai Chang; Fang-Yu Lin; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Min-Hung Chen; Shella Permatasari Santoso; Chang-Wei Hsieh (Food Packaging and Shelf Life, 2023)

Direct and alternating current electric fields affect pectin esterase and cellulase in tomato (Solanum lycopersicum L.) fruit during storage - Chao-Kai Chang; Sheng-Yen Tsai; Mohsen Gavahian; Kuan-Chen Cheng; Chih-Yao Hou; Bara Yudhistira; Shu-Hui Lin; Shella Permatasari Santoso; Chang-Wei Hsieh (Postharvest Biology and Technology, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

SERS-based rapid susceptibility testing of commonly administered antibiotics on clinically important bacteria species directly from blood culture of bacteremia patients - Yin-Yi Han; Jann-Tay Wang; Wei-Chih Cheng; Ko-Lun Chen; Yi Chi; Lee-Jene Teng; Juen-Kai Wang; Yuh-Lin Wang (World Journal of Microbiology and Biotechnology, 2023)
Bloodstream infections are a growing public health concern due to emerging pathogens and increasing antimicrobial resistance. Rapid antibiotic susceptibility testing (AST) is urgently needed for timely and optimized choice of antibiotics, but current methods require days to obtain results. Here, we present a general AST protocol based on surface-enhanced Raman scattering (SERS-AST) for bacteremia caused by eight clinically relevant Gram-positive and Gram-negative pathogens treated with seven commonly administered antibiotics. Our results show that the SERS-AST protocol achieves a high level of agreement (96% for Gram-positive and 97% for Gram-negative bacteria) with the widely deployed VITEK 2 diagnostic system. The protocol requires only five hours to complete per blood-culture sample, making it a rapid and effective alternative to conventional methods. Our findings provide a solid foundation for the SERS-AST protocol as a promising approach to optimize the choice of antibiotics for specific bacteremia patients. This novel protocol has the potential to improve patient outcomes and reduce the spread of antibiotic resistance.

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

University-driven coastal partnerships to address ghost gear pollution: A case study in Penghu Islands of Taiwan - Chih-Cheng Lin; Kuo-Huan Ting; Hao-Tang Jhan; Chung-Lun Liu; Li-Shu Chen; Wen-Hong Liu (Marine Policy, 2023)

Integrated ground and vertical measurement techniques to characterize overhead atmosphere: Case studies of local versus transboundary pollution - Chang-Feng Ou-Yang; Chih-Chung Chang; Sheng-Hsiang Wang; Charles C.-K. Chou; Ming-Tung Chuang; Tang-Huang Lin; Wei-Nai Chen; Ta-Chih Hsiao; Ming-Cheng Yen; Yueh-Chen Wang; Neng-Huei Lin; Jia-Lin Wang (Science of The Total Environment, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Improved bioremediation of PCDD/Fs contaminated soil by mycelium-free liquids induced by agro-industrial residues - Chih-Yu Cheng; Zhi-Feng Zhang; Acharee Kaewlaoyoong; Jing-Ting Huang; Nicholas Kiprotich Cheruiyot; Chitsan Lin; Hung-Chou Huang (Bioresource Technology Reports, 2023)

Improving Aquaculture Water Quality Using Dual-Input Fuzzy Logic Control for Ammonia Nitrogen Management - Hung-Chih Li; Ker-Wei Yu; Chang-Hua Lien; Chitsan Lin; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (Journal of Marine Science and Engineering, 2023)
In this paper, a closed-loop control system using dual-input fuzzy logic theory is proposed to improve the water quality of aquaculture. The new closed-loop control system is implemented on a Raspberry-Pi-embedded platform using Python programming. The proposed closed-loop control system integrates an RS485 function, a database transfer module, a simulating variable group function, and a trigger function import to achieve savings in human resources, power, and water consumption. The proposed closed-loop control system is equipped with an ammonia nitrogen sensor and solenoid valves for the water exchange. The experimental results demonstrate that the intelligent controller can rapidly eliminate ammonia nitrogen within the range of 2.0 ppm and maintain robust control in response to changes in ammonia nitrogen excretion from a school of fish. The experimental results provide insights into the relationship between tank capacity, water exchange solenoid valves, and ammonia nitrogen degradation time, which can be used to optimize aquaculture density and improve industrialization. The experimental results demonstrate that the savings for power and water can be achieved above 95%.

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Role of roasting in the formation of characteristic aroma of wuyi rock tea - Sijia Zhan; Zhibin Liu; Weiying Su; Chih-Cheng Lin; Li Ni (Food Control, 2023)

Selective accumulation of ionic nanocrystal H2 storage system as an in situ H2/boric acid nanogenerator fights against ethanol-induced gastric ulcers - Chih-Wei Chou; Wei-Tso Chia; Cam-Hoa Mac; Cheng-Yu Wu; Chun-Chieh Chen; Hsiang-Lin Song; Yi-Hsuan Lin; Yu-Jung Lin; Hsing-Wen Sung (Chemical Engineering Journal, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Modeling of an integrated H2S/NH3 scrubber and regeneration columns for coke oven gas purification - Hao-Jen Pan; Ming-Chun Fang; Jeffrey D. Ward; Hao-Yeh Lee; Hsun-Yu Lin; Cheng-Ting Hsieh; Chih-Lung Lee; Tzu-Hsien Huang; Yu-Chen Hsieh; Shih-Chieh Lin; Wei-Ti Chou (Journal of Cleaner Production, 2023)

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Promoting human rights for Taiwan’s fishermen: Collaboration with the primary source countries of Taiwan’s DWF migrant fishermen - Po-Chih Hung; Hsiao-Chien Lee; Chih-Cheng Lin; Wen-Hong Liu (Frontiers in Marine Science, 2022)
Taiwan is one of the largest distant water fishing (DWF) nations worldwide, and relies largely on the migrant labor to keep costs low. However, this industry has caused Taiwan to be listed in the 2020 “List of Goods Produced by Child Labor or Forced Labor” of the U.S. Department of Labor. In view of this, the Taiwanese government is actively adopting further management measures to supervise the domestic and foreign fishermen agencies. It is because the latter has been involved in many disputes, especially in recruitment, payroll, and labor contracts, which directly or indirectly affect the rights of migrant fishermen. On the other hand, although the C188 Work in Fishing Convention has stregthend the protection of the fishermen’s human rights, it still stays ambiguous in terms of private agency management. That is also why so many disputes have been caused in recent years.This study conducts a comparative analysis of the agency management systems in the primary source countries of Taiwan’s distant water fishing migrant fishermen (that is, Indonesia, the Philippines, and Vietnam), as well as interviews with distant water fishing stakeholders to provide insights on the improvement of agency management and migrant fishermen’s rights in Taiwan. The findings imply that the positive interaction, mutual trust, and understanding of laws and regulations between fishermen’s exporting and importing countries lead to future cross-national collaboration. This study suggests that the Taiwanese government should follow the spirit of the C188 but not be restricted to the Convention texts to amend or formulate regulations and policies of agencies for fully protecting the rights of migrant fishermen.

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Passive Cavitation Enhancement Mapping via an Ultrasound Dual-Mode phased array to monitor blood-brain barrier opening - Trung Nguyen Hoang; Hsiang-Ching Lin; Chih-Hong Tsai; Cheng-Kai Jan; Hao-Li Liu (Journal of Medical and Biological Engineering, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Cracking and Photo-Oxidation of Polyoxymethylene Degraded in Terrestrial and Simulated Marine Environments - Chih-Cheng Tang; Ying-Ting Chen; Yi-Ming Zhang; Huey-Ing Chen; Peter Brimblecombe; Chon-Lin Lee (Frontiers in Marine Science, 2022)
Marine plastic debris is an environmental problem, and its degradation into microplastics (1-5000 μm) introduces them into the food chain. In this study, small polyoxymethylene (global production ~3000 Tg per year) pellets were exposed in terrestrial and simulated marine environments to heat and light, resulting in cracking during decay with increasing IR absorption (OH-bonds). Furthermore, sunlight over three years reduced pellet mass and diameter (~10% and ~40%), initially yielding 100-300 μm fragments. Changes under UV irradiation were smaller as it could not penetrate into particle interiors. Characteristic spacing of surface striations (100-300 µm) initiated radial cracks to pellet interiors, and breakdown ultimately meant 95% of particles were <300 µm, which are potentially incorporated in marine turbidites.

Potential Plasticity of Artificial Feed Preference in Juvenile Pharaoh Cuttlefish (Sepia pharaonis) Through Progressive Training Programs - Chia-Huan Ma; Chih-Hung Lin; Yung-Cheng Chang; Hung-Tai Lee; Chyng-Hwa Liou; Te-Hua Hsu (Frontiers in Marine Science, 2022)
The cuttlefish is a commercially important marine species across the world; however, due to the lack of appropriate artificial feed, there is limited future aquaculture development of the cuttlefish. We proposed a novel process comprising (1) feed preference tests and (2) progressive training programs. Through this process, artificial diets can become more suitable for pharaoh cuttlefish ( Sepia pharaonis ). Feed preference tests (based on vision, touch, and smell) revealed that pharaoh cuttlefish preferred rod-shaped feed to flat rod-shaped or ball-shaped feed, moist feed over dry feed (DF), and DF with agar coating to DF without agar coating. Without olfactory training, some cuttlefish refused to eat artificial feed and eventually died. Through progressive training programs (3- and 6-week programs), a survival rate of >80% was achieved. Although the artificial diets examined in this study resulted in a lower conversion ratio for S. pharaonis than for fresh shrimp, available artificial feed can potentially be adopted for cuttlefish aquaculture through the use of our progressive training program.

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

L-Theanine Ameliorated Rotenone-Induced Parkinsonism-like Symptoms in Rats - Cheng-Neng Chen; Mao-Hsien Wang; Hung-Sheng Soung; Shu-Mei Chen; Chih-Hsiang Fang; Yi-Wen Lin; Hsiang-Chien Tseng (Neurotoxicity Research, 2022)

Investigating the Transcriptomic and Expression Presence-Absence Variation Exist in Japanese Eel (Anguilla japonica), a Primitive Teleost - Yung-Sen Huang; Chung-Yen Lin; Wen-Chih Cheng (Marine Biotechnology, 2021)

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Correction to: Delineation of potential hot spots of aeolian dust using normalized difference water index - Chao-Yuan Lin; Shu-Fen Tsai; Chih-Yun Wang; Cheng-Yu Lin (Theoretical and Applied Climatology, 2021)

Delineation of potential hot spots of aeolian dust using normalized difference water index - Chao-Yuan Lin; Shu-Fen Tsai; Chih-Yun Wang; Cheng-Yu Lin (Theoretical and Applied Climatology, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Characterization Of Secondary Metabolites From The Rhizome Of Cynara Scolymus And Their Antioxidant Properties - Chia-Lin Lee; Kuo-Chen Liao; Chien-Chih Chen; Yen-An Lin; Tung-Ying Wu; Yun-Lian Jhan; Chao-Jung Chen; Juan-Cheng Yang; Yang-Chang Wu (Natural Product Research, 2021)

Androgenic Sensitivities and Ovarian Gene Expression Profiles Prior to Treatment in Japanese Eel (Anguilla japonica) - Yung-Sen Huang; Wen-Chih Cheng; Chung-Yen Lin (Marine Biotechnology, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Cabbage defense response provoked by Trichoderma Th-LAAO - Chia-Min Liu; Shu-Ying Liu; Chuan-Kai Liao; Chaur-Tsuen Lo; Kuo-Chih Lin; Kou-Cheng Peng (Archives of Microbiology, 2021)

The Biomechanical Response of the Lower Cervical Spine Post Laminectomy: Geometrically-Parametric Patient-Specific Finite Element Analyses - Mohammad Nikkhoo; Chih-Hsiu Cheng; Jaw-Lin Wang; Chi-Chien Niu; Mohamad Parnianpour; Kinda Khalaf (Journal of Medical and Biological Engineering, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

Concurrent increases in post-pacing action potential duration and contractility predict occurrence of ventricular arrhythmia - Chih-Min Liu; Feng-Zhi Lin; Yao-Chang Chen; Yung-Kuo Lin; Yen-Yu Lu; Cheng-I Wu; Satoshi Higa; Shih-Ann Chen; Yi-Jen Chen (Pflügers Archiv - European Journal of Physiology, 2020)

Correction to: Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Complete genome sequences of two novel dicistroviruses detected in yellow crazy ants (Anoplolepis gracilipes) - Chih-Chi Lee; Chun-Yi Lin; Hung-Wei Hsu; Chin-Cheng Scotty Yang (Archives of Virology, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Impact of Prolonged Tablet Computer Usage with Head Forward and Neck Flexion Posture on Pain Intensity, Cervical Joint Position Sense and Balance Control in Mechanical Neck Pain Subjects - Cheng-Chieh Lin; Siang-Hua Hua; Cheng-Li Lin; Chih-Hsiu Cheng; Jen-Chieh Liao; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2020)

Diverse Community Structures in the Neuronal-Level Connectome of the Drosophila Brain - Chi-Tin Shih; Yen-Jen Lin; Cheng-Te Wang; Ting-Yuan Wang; Chih-Chen Chen; Ta-Shun Su; Chung-Chuang Lo; Ann-Shyn Chiang (Neuroinformatics, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

Development and evaluation of a storm surge warning system in Taiwan - Mei-Ying Lin; Wen-Yih Sun; Ming-Da Chiou; Chih-Ying Chen; Hao-Yuan Cheng; Cheng-Hsin Chen (Ocean Dynamics, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Evaluation of Lactic Acid Bacteria Isolated from Fermented Plant Products for Antagonistic Activity Against Urinary Tract Pathogen Staphylococcus saprophyticus - Cheng-Chih Tsai; Tzu-Min Lai; Pei-Pei Lin; You-Miin Hsieh (Probiotics and Antimicrobial Proteins, 2018)

Adaptive Weighted Nonlinear Least Squares Method for Fluorodeoxyglucose Positron Emission Tomography Quantification - Sheng-Cheng Huang; Liang-Chih Wu; Wen-Chen Lin; Kang-Ping Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2018)

Kinematic, Kinetic and Surface Electromyography Analysis Following Zygomatic Fracture Reconstruction - Cheng-I Yen; Pang-Yun Chou; Chih-Hao Chen; Tzu-Yin Chen; Chien-Tzung Chen; Wen-Yen Lin; Ming-Yih Lee (Journal of Medical and Biological Engineering, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

One-step reverse transcription loop-mediated isothermal amplification for the detection of Capsicum chlorosis virus in Phalaenopsis orchids - Cheng-Ping Kuan; Yu-Fei Lin; Yu-Chun Lin; Chin-Chih Chen (Journal of General Plant Pathology, 2016)

Characteristics of soil CO2 efflux under an invasive species, Moso bamboo, in forests of central Taiwan - I-Fang Hsieh; Tomonori Kume; Meng-Ying Lin; Chih-Hsin Cheng; Takeshi Miki (Trees, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Paraquat Induces Cell Death Through Impairing Mitochondrial Membrane Permeability - Chuen-Lin Huang; Chih-Chang Chao; Yi-Chao Lee; Mei-Kuang Lu; Jing-Jy Cheng; Ying-Chen Yang; Vin-Chi Wang; Wen-Chang Chang; Nai-Kuei Huang (Molecular Neurobiology, 2016)

Serotonin Receptor 2B Mediates Mechanical Hyperalgesia by Regulating Transient Receptor Potential Vanilloid 1 - Yeu-Shiuan Su; Yuan-Yi Chiu; Shih-Yuan Lin; Chih-Cheng Chen; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

One-step Real-time Food Quality Analysis by Simultaneous DSC–FTIR Microspectroscopy - Shan-Yang Lin; Chih-Cheng Lin (Critical Reviews in Food Science and Nutrition, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Multi-muscle coordination during a challenging stance - Wen-Chieh Yang; Chih-Hsiu Cheng; Hsing-Kuo Wang; Kwan-Hwa Lin; Wei-Li Hsu (European Journal of Applied Physiology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

Cathepsin B is involved in the heat shock induced cardiomyocytes apoptosis as well as the anti-apoptosis effect of HSP-70 - Shu-Fen Hsu; Chuan-Chih Hsu; Bor-Chih Cheng; Cheng-Hsien Lin (Apoptosis, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Human recombinant factor VIIa may improve heat intolerance in mice by attenuating hypothalamic neuronal apoptosis and damage - Chuan-Chih Hsu; Sheng-Hsien Chen; Cheng-Hsien Lin; Ming-Chi Yung (Apoptosis, 2014)

Investigating the interactive mechanisms between surface water and groundwater over the Jhuoshuei river basin in central Taiwan - Fi-John Chang; Cheng-Hsien Lin; Kuang-Chih Chang; Yu-Hsuan Kao; Li-Chiu Chang (Paddy and Water Environment, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Use of motor abundance in old adults in the regulation of a narrow-based stance - Wei-Li Hsu; Kwan-Hwa Lin; Rong-Sen Yang; Chih-Hsiu Cheng (European Journal of Applied Physiology, 2014)

Altered molecular repertoire of immune system by renal dysfunction in the elderly: is prediction and targeted prevention in the horizon? - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Chih-Kang Chiang; Kuo-Cheng Lu (EPMA Journal, 2013)
Background Patients on chronic hemodialysis (HD) have impaired cellular and humoral immunity. The percentage of elderly people among the total population in Taiwan is increasing dramatically, and HD is the primary alternative for renal replacement therapy when renal function declines. Activated vitamin D is widely used in HD patients with secondary hyperparathyroidism (SHPT) and is a well-known immunomodulatory agent. Personalized medicine and integrative medical approach has been a trend in current clinical practice. Can we improve their immune function using vitamin D in spite of the mineral aspect? Here, we investigated the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and T cell differentiation in chronic HD patients. Methods Forty patients with chronic HD were enrolled. HD patients with SHPT had been treated with activated vitamin D for 3 months. Peripheral blood mononuclear cells obtained from the patients were cultured and stimulated by mitogens, and T cells were analyzed by flow cytometry. Serum 25(OH)D levels were detected by enzyme-linked immunosorbent assay. Results The incidence of T cell differentiation to the T helper cell (Th)2 subtype was more prevalent in the elderly group than in the controls ( p = 0.001). Th2 differentiation was also correlated with age ( p = 0.004) and serum 25(OH)D levels ( p < 0.05). After treated with activated vitamin D, the level of Th1 cytokines decreased while the Th2 cytokine level increased in the sera ( p < 0.05). The T cell differentiation tended toward the Th2 subtype ( p = 0.027) after treatment of activated vitamin D in SHPT patients. Conclusions These results demonstrated that Th2 differentiation is correlated with age and the serum 25(OH)D level of patients. Treatment with activated vitamin D influenced T cell differentiation and cytokine expression in SHPT patients. Taking vitamin D is the possible prediction and targeted treatment in the immune dysfunction in chronic HD patients.

Retrofit of steam power plants in a steel mill - Cheng-Liang Chen; Chih-Yao Lin (Clean Technologies and Environmental Policy, 2013)

Application of a feature-based approach to debris flow detection by numerical simulation - Chih-Wei Lin; Cheng-Wu Chen; Wen-Ko Hsu; Chia-Yen Chen; Chung-Hung Tsai; Yi-Ping Hung; Wei-Ling Chiang (Natural Hazards, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Erratum to: Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tzeng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Super-ensemble of three RCMs for climate projection over East Asia and Taiwan - Chung-Ming Liu; Ming-Chin Wu; Sahana Paul; Ying-Chen Chen; Shu-Hua Lin; Wei-Shiang Lin; Yen-Chih Lee; Huang-Hsung Hsu; Ren-Yow Tseng; Cheng-Ta Chen (Theoretical and Applied Climatology, 2011)

Molecular characterization of a phenylalanine ammonia-lyase gene (BoPAL1) from Bambusa oldhamii - Lu-Sheng Hsieh; Yi-Lin Hsieh; Chuan-Shan Yeh; Chieh-Yang Cheng; Chien-Chih Yang; Ping-Du Lee (Molecular Biology Reports, 2011)

Anti-herpes simplex virus effects of berberine from Coptidis rhizoma, a major component of a Chinese herbal medicine, Ching-Wei-San - Lengsu William Chin; Yu-Wen Cheng; Shih-Shen Lin; Ya-Yun Lai; Long-Yau Lin; Ming-Yung Chou; Ming-Chih Chou; Chi-Chiang Yang (Archives of Virology, 2010)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

The predictive role of E2-EPF ubiquitin carrier protein in esophageal squamous cell carcinoma - Miao-Fen Chen; Kuan-Der Lee; Ming-Shian Lu; Chih-Cheng Chen; Ming-Ju Hsieh; Yun-Hen Liu; Paul-Yang Lin; Wen-Cheng Chen (Journal of Molecular Medicine, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Co-contraction of cervical muscles during sagittal and coronal neck motions at different movement speeds - Chih-Hsiu Cheng; Kwan-Hwa Lin; Jaw-Lin Wang (European Journal of Applied Physiology, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Biodegradation Kinetics and Effects of Operating Parameters on the Performance of a Methyl Tert-Butyl Ether Degrading Biofilter - Yi-Cheng Chiu; Chi-Wen Lin; Tsang-Chih Kao; Xiao-Yan Tang (Water, Air, & Soil Pollution, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Digestion Methods for Total Heavy Metals in Sediments and Soils - Zeng-Yei Hseu; Zueng-Sang Chen; Chen-Chi Tsai; Chun-Chih Tsui; Shuang-Fu Cheng; Chyan-Lan Liu; Haw-Tarn Lin (Water, Air, & Soil Pollution, 2002)

Temporal and spatial expression of biologically active human factor VIII in the milk of transgenic mice driven by mammary-specific bovine α-lactalbumin regulation sequences - Chuan-Mu Chen; Chih-Hong Wang; Shinn-Chih Wu; Chih-Cheng Lin; Shwu-Hwa Lin; Winston T.K. Cheng (Transgenic Research, 2002)